The Effect Of Child Work Behavior On Hemoglobin Levels - Rahmi Amir; Rina Rina; Amir Patintingan (Malahayati Nursing Journal, 2022)
Abstract. The relationship between the work behavior of crew members on hemoglobin levels, with unhealthy work behavior variables, can cause a decrease or increase in workers' hemoglobin levels. The research was carried out at the Nusantara Port of Parepare KM. Queen Soya. Data processing using Chi-square test. The results of the study of P 0.05 was 0.36, indicating that there was no significant effect on Hb levels. Keywords: Blood, Hemoglobin, workers